MP3s Are Killing Home Taping: The Rise of Internet Distribution and Its Challenge to the Major Label Music Monopoly1. - McLeod, Kembrew (Popular Music & Society, 2005)
The phrase “home taping is killing music”—a slogan invented and heavily promoted by major labels to combat the unauthorized duplication of music in the early-1980s—now sounds quaint after the rise of digital distribution. Because the legal arguments surrounding the trading of copyrighted music on file-sharing networks have been extensively debated elsewhere, this article primarily focuses on the way this alternative distribution system poses a very real challenge to major labels. That music monopoly, which has been in place for a century, was able to secure its dominance because it controlled the means of production—something that is no longer the case, because recording, production and distribution costs have radically dropped in price since the 1990s. This article, which operates in a journalistic mode, places into historical context the 1990s compact disc boom and the subsequent rise of digital distribution. The consumer-led file-sharing explosion forced an unwilling music industry into the online marketplace, something that this article argues has been a boon for those working outside of the major label system. This has opened the door for small labels and independent artist-entrepreneurs to use these relatively inexpensive technologies to disseminate their music and circumvent the clogged, payola-drenched playlists of corporate radio.